2002
DOI: 10.1677/joe.0.1720441
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of testosterone propionate, oestradiol benzoate, ICI 182,780, tamoxifen and raloxifene on hypothalamic differentiation in the female rat

Abstract: Hypothalamic differentiation in the female rat during the neonatal period is critically dependent on the steroid milieu, as permanent changes in reproductive function are observed after administration of oestradiol and testosterone during such a critical stage. Selective oestrogen modulators (SERMs) constitute a family of drugs that, depending on the tissue, are able to exert oestrogenic or antioestrogenic actions. The present experiments were conducted to analyse whether the SERMs, tamoxifen and raloxifene, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…35 mg oestradiol benzoate used in this study is based on our previous study (Alexanderson et al 2007) since this dose is known to affect insulin sensitivity and metabolism in adult female rats. There is no standardised dose or administration procedure when studying the postnatal effects of oestrogenisation, several different doses and administration regimes have been used (Arai 1964, Pinilla et al 2002, Sotomayor-Zarate et al 2008. However, the injected dose used in our study concurs with other studies where 0 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…35 mg oestradiol benzoate used in this study is based on our previous study (Alexanderson et al 2007) since this dose is known to affect insulin sensitivity and metabolism in adult female rats. There is no standardised dose or administration procedure when studying the postnatal effects of oestrogenisation, several different doses and administration regimes have been used (Arai 1964, Pinilla et al 2002, Sotomayor-Zarate et al 2008. However, the injected dose used in our study concurs with other studies where 0 .…”
Section: Discussionsupporting
confidence: 85%
“…However, the injected dose used in our study concurs with other studies where 0 . 1 mg oestradiol benzoate (Pinilla et al 2002) or 0 . 1 mg oestradiol valerate (Sotomayor-Zarate et al 2008) has been injected into 1-day-old female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects might underlie the changes in reproductive function previously identified in adult animals neonatally exposed to EV or TP (8,14,22).…”
Section: Discussionmentioning
confidence: 92%
“…The doses of EV and TP were chosen based on previous studies of adult and prepubertal rats (7,13). In choosing the dose of TP, we considered the report of Pinilla et al (14), which used 0.1 mg estradiol benzoate and 1.25 mg TP for 1-day postpartum (P1) rats. DHT dose was chosen based on the report of Arai et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, conflicting results on the presence or absence of any estrogenic activity of raloxifene on hypothalamicpituitary function have been presented (14)(15)(16). In this context, data from our laboratory indicated that administration of raloxifene during the neonatal period of hypothalamic sex differentiation induced an estrogen-like effect on the functional organization of the hypothalamic -pituitary unit (17,18); however, raloxifene did not act in the same way as estrogen on the neuronal systems controlling sexual receptivity in the female rat (18). In adult animals, raloxifene increased serum prolactin concentrations and decreased luteinizing hormone (LH) levels in ovariectomized rats, thus indicating an activational estrogenic action of this SERM in the regulation of hypothalamic -pituitary function (19).…”
Section: Introductionmentioning
confidence: 99%